Data-Driven Analysis of EFL Teaching Factors: Classroom Environment and Collaboration Effects on Students’ Performance: A Study at Secondary Schools of Guiyang City, China - Minfang, Lou; Keat, Ooi Boon; Azar, Ali Sorayyaei (International Journal of Learning, Teaching and Educational Research, 2025)
This study aims to establish and validate a theoretical framework to examine the effects of the English as a Foreign Language (EFL) classroom environment and collaborative learning on students’ performance. Through rigorous data analysis, this research seeks to enhance understanding of how these factors influence student outcomes in English language learning. A quantitative research design was employed, using a questionnaire to collect data from 293 English teachers at secondary schools across the Nanming District, Guiyang City. The data were analyzed using SmartPLS for structural equation modeling. The results indicate that both the EFL classroom environment and collaborative learning have statistically significant positive relationships with student performance (p < 0.05). These findings underscore the importance of fostering a supportive classroom atmosphere and implementing collaborative learning strategies to enhance educational outcomes. Based on the results, it is recommended that education authorities encourage English teachers to adopt collaborative learning methods and update their pedagogical skills to better facilitate student engagement and performance. Additionally, schools should be equipped with essential teaching resources and effective classroom environments to support the teaching-learning process.